Value and limitations of sonography in kidney transplant recipients with special attention to the resistive index – An update - Stigler, Julia; Tiefenthaler, Martin (Frontiers in Nephrology, 2022)
Kidney transplantation has become the standard treatment for end-stage renal disease. Even though the success rates are high, early and late post-transplant complications remain a major clinical problem due to the risk of graft failure. Therefore, it is of highest interest to early diagnose post-transplant complications. Ultrasound with color Doppler analysis plays a crucial role in imaging mechanical and vascular complications. In this article, we give an update of the visualizable complications in kidney transplant recipients and discuss the value of resistive index (RI) measurement with its limitations in allograft rejection.